2022
DOI: 10.3389/frhs.2022.896885
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Clinical Champions and Their Impact on Clinician Behavior Change: The Need for Causal Pathway Mechanisms

Abstract: BackgroundThe clinical champion approach is a highly utilized implementation strategy used to mitigate barriers and improve outcomes of implementation efforts. Clinical champions are particularly effective at addressing provider-level barriers and promoting provider-behavior change. Yet, the specific causal pathways that explain how clinical champions impact provider behavior change have not been well-explicated. The current paper applies behavior change models to develop potential causal pathway mechanisms.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 79 publications
(312 reference statements)
2
17
0
Order By: Relevance
“…In the EPIC project the practice champions self-identified. The implementation science literature shows that champions can increase the adoption of an innovation at multiple levels, but their success often depends on educating and persuading others through social influence 46. This is confirmed in our study, the most successful EPIC champions were collaborative and had a strong passion for implementing a palliative approach to care in their practice.…”
Section: Discussionsupporting
confidence: 81%
“…In the EPIC project the practice champions self-identified. The implementation science literature shows that champions can increase the adoption of an innovation at multiple levels, but their success often depends on educating and persuading others through social influence 46. This is confirmed in our study, the most successful EPIC champions were collaborative and had a strong passion for implementing a palliative approach to care in their practice.…”
Section: Discussionsupporting
confidence: 81%
“…The clinical champion approach has been linked to reduction of implementation barriers and can promote behavior change across providers. 18 8: Development of Palliative Occupational Therapy (OT) Liaison Role: A formal job description and role delineation is developed for OTPs on palliative care IDTs. Rationale : OTPs facilitate participation in meaningful activities and enhance quality of life for people nearing end-of-life. 2 Living while dying is an occupation, 19 and fostering independence during this vulnerable time may allow a seriously ill person to maintain a level of autonomy as well as much desired social connections.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical champion approach has been linked to reduction of implementation barriers and can promote behavior change across providers. 18…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have reported that clinical champions are instrumental in the quicker initiation of interventions, assist in overcoming institutional barriers, and can motivate and involve staff in clinical trials. 39,40 We report that every year, a trained EM provider will between ve and 115 seriously ill older adult patients depending on the ED volume, patient mix, and geographic setting, among other factors. This wide range of encounter highlights the diversity in the patient population that visit the ED, and the need for each ED to conduct a needs assessment, create ED-speci c standard operating procedures in engaging qualifying patients in SI conversations, and provide a conducive environment for SI conversations in their respective EDs.…”
Section: Discussionmentioning
confidence: 99%